(untitled) (Nepal Journal of Health Sciences, 2025)
Introduction: Root canal treatment is a routine endodontic procedure that preserves teeth affected by pulpal or periapical disease. Assessing its prevalence and quality provides insight into patient needs and outcomes. Objective: To evaluate the prevalence and characteristics of root canal treatment among patients at a tertiary care dental center. Methods: A retrospective cross-sectional study was conducted at the Department of Oral Medicine and Radiology of Kathmandu University School of Medical Sciences, Dhulikhel Hospital, Kavre, Nepal. A total of 513 panoramic radiographs of adults (January 2022- January 2023) were reviewed. Data on number and distribution of root canal treated teeth, according to gender, age, jaw, tooth type, quality of obturation, and periapical pathology, were analyzed. Ethical approval was obtained. Results: A total of 387 root canal treated teeth were identified. Root canal treatment was slightly more common in females (51.3%) and most frequent in patients aged 20-30 years. Maxillary teeth accounted for 55.04% of treated teeth, with the maxillary first molar (14.99%) and central incisor (11.37%) being most common. In the mandible, the first molar (21.18%) was most frequently treated. While most obturations were adequate,underfilling (18.34%), overfilling (2.06%), and periapical radiolucency (10.07%) were observed. Conclusion: Root canal treatment was more common in younger individuals, predominantly involving molars. Although most treatments were of acceptable quality, deficiencies and periapical pathology were also noted which emphasizes the need for precise treatment and long-term follow-up